THE METHOD OF TRANSFORMATION IN DESCRIPTIVE LINGUISTICS - Konul H. Mamedova (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
As we know the method of transformation was proposed by Z. Harris who was the outstanding delegate of descriptive linguistics, later was used by his student N. Chomsky. By creating the transformation model of generative grammar N. Chomsky established the difference in descriptive linguistics. His new grammatical concept arouse interest not only of American linguists, but also the linguists of other countries who were investigating American hindi languages. But this innovation itself originated from the descriptive linguistics too. Linguists describe the language materials in a new form with transformation method and research the syntagmatic sides of syntactic structure. According to Harris the method of transformation filled the gap in descriptive analysis. It is necessary for the paradigmatic ranking of sentences to have connection between them and be the similar components for transformation. We can distinguish the kernel sentences and their transformations with this method and we can describe the conversion from simple forms into complex ones. We have learned the general structure of the language and apply it practically in the linguistics. As well as we have solved the concept of word-groups with the theoretical significance of transformation. This problem is not solved in non-transformational grammar and distinguishing the parts of the sentence. The method of transformation approaches with the same criterion of all types of sentences, separates them into kernel and transforms and uses all parts of syntax such as deletion, permutation, substitution, functional words according to the transformation rules and confirms them. Transformation method is used in machine translation grammar, as well as teaching the foreign languages and in preparation teaching aids of these languages from transformation in terms of syntax. This method is also widely used for learning speech activity in psycholinguistics, annotation of the text in information science. From the above mentioned, we can conclude that the method of transformation, although it seems simple, has a broad explanatory power. Based on this method, you can take the simplest linguistic core of the language and create complex structures from it. Moving, replacing, substituting, reducing and getting rid of linguistic units is carried out precisely through transformation. Transformations were carried out to a large extent by operations that could not be performed by distribution methods. It is possible to explain speech activity and the processes of logical research of sentences also in the transformational analysis of linguistic materials.